Pengaruh Komposisi Hidroksi Propil Metil Selulosa K-15 dan Etil Selulosa N-22 terhadap Prosentase Kelembapan Air dan Pelepasan Meloksikam dari Sediaan Plester (The Influence of Hidroxy Propyl Methyl Cellulose K-15 and Ethyl Cellulose N-22 Ratio on Procent - Monica Iwud Rully Pramesthie; Lidya Ameliana; Budipratiwi Wisudyaningsih (UPT Percetakan dan Penerbitan Universitas Jember, 2014)
The present research has been undertaken with the aim to develop a transdermal patch of meloxicam with ratio of hydroxy propyl methyl cellulose (HPMC) K-15 and ethylcellulose (EC)N-22 as a matrix were 1:9 (Formula 1), 2:8 (Formula 2), 3:7 (Formula 3).The physicochemical parameters like organoleptic and % moisture content were evaluated. Released test using dissolution apparatus were carried out in 500 mL of phosphate buffer saline pH 7.4 ± 0.05 at temperature 37 ± 0.5°C with speed of swirl 50 rpm. Results were analyzed by statistic programmed of SPSS using one way analysis of variance with degree of believed 95% (α = 0,05).The results of evaluation of patch dosage, transdermal patches were found yellow, odorless and dry. Result of moisture content F(1) 1.168 ± 0.009 %; F(2) 1.841 ± 0.019 % and F(3) 2.584 ± 0.025 %. Result of in vitro drug release F(1) 364.865 ± 0.701 µg/cm2.menit1/2; F(2) 397.212 ± 0.441 µg/cm2.menit1/2 and F(3) 439.277 ± 0.559 µg/cm2.menit1/2. It can be concluded that the combination ofHPMC K-15 and EC N-22 at ratio 7:3 was the best choice for manufacturing transdermal patch based on physicochemical and the release profile. Keywords: transdermal patch, meloxicam, hydroxypropylmethyl celulosa, ethylcellulosa